Performance of the Colloidal Gold Immunochromatography of Cryptococcal Antigen on Bronchoalveolar Lavage Fluid for the Diagnosis of Pulmonary Cryptococcosis - Ning Zhu; Shanhong Lin; Xingbei Weng; Weijie Sun; Xueqin Chen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. This study aimed to investigate the efficacy of the colloidal gold immunochromatography method in the detection of Cryptococcus antigen in bronchoalveolar lavage fluid (BALF) for pulmonary cryptococcosis (PC) diagnosis. Methods. A total of 111 patients with clinically suspected PC who were finally diagnosed with nonhuman immunodeficiency virus infection and hospitalized in the Ningbo First Hospital from March 2017 to December 2021 were retrospectively analyzed. All the confirmed cases were divided into two groups as follows: the PC group (33 cases) and the non-PC group (78 cases). All the patients were subjected to serum and BALF cryptococcal capsular polysaccharide antigen-lateral flow immunochromatographic assay (CrAg-LFA) and etiological culturing. Results. In the PC group, serum CrAg-LFA was positive for 24 and negative for 9 cases, serum Cryptococcus culture was positive for 1 and negative for 32 cases, BALF CrAg-LFA was positive for 31 and negative for 2 cases, and BALF Cryptococcus culture was positive for 9 and negative for 24 cases. In the non-PC group, serum CrAg-LFA was positive for 1 and negative for 77 cases, serum culture was negative in all the cases, and both BALF CrAg-LFA and culture were negative in all the cases. The sensitivity, specificity, and accuracy of BALF CrAg-LFA for PC diagnosis were 93.9%, 100%, and 98.2%, respectively, whereas those of BALF culture were 27.3%, 100%, and 78.4%, respectively. The sensitivity and accuracy of BALF CrAg-LFA were higher than that of serum CrAg-LFA and BALF etiological culture with statistically significant differences (p<0.05). Conclusion. The diagnostic value of BALF CrAg-LFA for PC is superior to that of serum CrAg-LFA and BALF etiological culture.